2010
DOI: 10.1111/j.1540-5885.2010.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplier and Customer Integration on Product Innovation and Performance: Empirical Evidence in Hong Kong Manufacturers

Abstract: While the beneficial impacts of supplier and customer integration are generally acknowledged, very few empirical research studies have examined how an organization can achieve better product performance through product innovation enhanced by such integration. This paper thus examines the impact of key supplier and customer integration processes (i.e., information sharing and product codevelopment with supplier and customer, respectively) on product innovation as well as their impact on product performance. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
310
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(330 citation statements)
references
References 115 publications
(160 reference statements)
12
310
1
7
Order By: Relevance
“…This necessitates collaboration with external organizations such as suppliers (Un, et al 2010). The advantages of collaborating with suppliers have been demonstrated in previous research, where benefits include flexibility (Riege 2003), speed (Brown & Eisenhardt 1995;Langerak & Hultink 2008), improved innovation (Lau, et al 2010), access to market information (Miotti & Sachwald 2003), and access to the supplier's capabilities (Oh & Rhee 2010). On the other hand, in order to achieve these benefits, it is crucial to recognize what the above quote represents; collaboration involves being friends as well as enemies at the same time.…”
Section: Introductionmentioning
confidence: 93%
“…This necessitates collaboration with external organizations such as suppliers (Un, et al 2010). The advantages of collaborating with suppliers have been demonstrated in previous research, where benefits include flexibility (Riege 2003), speed (Brown & Eisenhardt 1995;Langerak & Hultink 2008), improved innovation (Lau, et al 2010), access to market information (Miotti & Sachwald 2003), and access to the supplier's capabilities (Oh & Rhee 2010). On the other hand, in order to achieve these benefits, it is crucial to recognize what the above quote represents; collaboration involves being friends as well as enemies at the same time.…”
Section: Introductionmentioning
confidence: 93%
“…Innovation plays a crucial role in fostering the long-term survival of firms, in determining the firm"s success, sustaining its global competitiveness and it is linked with competitive advantage and economic consequences (Porter, 1990;Lau et al, 2010). Various definitions of innovation describes it as the generation of creative ideas, acceptance and implementation of such creative new ideas within the organization into processes, products or services (Anderson et al, 2004;Schulze et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…If it is true that arguments are found pointing to a positive effect of this attribute on operational performance, sustained by economies of scale and reduced fixed costs Timotthy, 2000, Orlitzky, 2001) and in diversifying the range of products (services) produced (rendered) (Lau et al, 2010, Yam et al, 2011, the fact remains that arguments can be found pointing in the opposite direction. In small and micro enterprises in particular, an individual or family, characterized by a reduced propensity to risk and very careful analysis of investments, simultaneously perform the role of owner and manager, possibly conditioning performance.…”
Section: Methodsmentioning
confidence: 99%